Olfactory Neuroblastoma: A Rare Cause of External Ophthalmoplegia, Proptosis and Compressive Optic Neuropathy - Ömer Kartı; Mehmet Özgür Zengin; Ozan Çelik; Taşkın Tokat; Tuncay Küsbeci (Türk Oftalmoloji Dergisi)
Olfactory neuroblastoma (ONB), which is a neuroectodermal tumor of the nasal cavity, is a rare and locally aggressive malignancy that may invade the orbit via local destruction. In this study, we report a patient with proptosis, external ophthalmoplegia, and compressive optic neuropathy caused by ONB. A detailed clinical examination including ocular imaging and histopathological studies were performed. The 62-year-old female patient presented to our clinic with complaints of proptosis and visual deterioration in the left eye. Her complaints started 2 months prior to admission. Visual acuity in the left eye was counting fingers from 2 meters. There was relative afferent pupillary defect. She had 6 mm of proptosis and limitation of motility. Fundus examination was normal in the right eye, but there was a hyperemic disc, and increased vascular tortuosity and dilation of the retinal veins in the left eye. Computerized tomography and magnetic resonance imaging of the brain and orbits demonstrated a large heterogeneous mass in the left superior nasal cavity with extensions into the ethmoidal sinuses as well as into the left orbit, compressing the medial rectus muscle and optic nerve. Endoscopic biopsy of the lesion was consistent with an ONB (Hyams’ grade III). Orbital invasion may occur in patients with ONB. Therefore, it is important to be aware of this malignancy because some patients present with ophthalmic signs such as external ophthalmoplegia, proptosis, or compressive optic neuropathy.